2009
DOI: 10.1111/j.1475-1313.2009.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Bifocals and Down’s syndrome: correction or treatment?

Abstract: Bifocals are an effective correction for the reduced accommodation in children with DS and also act to improve accommodation with a success rate of 65%. Bifocal wear can therefore be temporary, i.e. a 'treatment' for the deficit, in at least one third of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 7 publications
4
34
1
Order By: Relevance
“…Myopic children are prescribed a full correction at a time when distance targets become of interest. Since 2004, children with an accommodative deficit and/or strabismus at near have been prescribed bifocals; for those who were emmetropic, plano-distance bifocals were prescribed 14 18 23 24…”
Section: Methodsmentioning
confidence: 99%
“…Myopic children are prescribed a full correction at a time when distance targets become of interest. Since 2004, children with an accommodative deficit and/or strabismus at near have been prescribed bifocals; for those who were emmetropic, plano-distance bifocals were prescribed 14 18 23 24…”
Section: Methodsmentioning
confidence: 99%
“…1,5 A recent study supports the explanation of sensory deficits based on observed improvements of accommodative accuracy in young subjects with DS after a period of bifocal wear. 13 The authors of that study suggested that the improvement would not have occurred if accommodation were limited by mechanical deficits. 13 Knowledge of accommodative dysfunction in individuals with DS is limited to lag.…”
mentioning
confidence: 97%
“…13 The authors of that study suggested that the improvement would not have occurred if accommodation were limited by mechanical deficits. 13 Knowledge of accommodative dysfunction in individuals with DS is limited to lag. One previous study attempted to measure accommodative amplitudes in these subjects, 2 but a later publication by the same laboratory acknowledged that this goal may not have been met.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…One35 reported that all 40 children (with previous hypoaccommodation) accommodated better with their bifocals and 26/40 (65%) also demonstrated better accommodation through the distance part of the lens, implying improved active accommodation rather than just the passive optical enhancement of accuracy of near viewing. The other36 reported that all 11 children improved the accuracy of their accommodation through the bifocal segment but not through the upper segment of their glasses.…”
Section: Resultsmentioning
confidence: 99%